Answer:
(i)unique solution
Explanation:
We solve for x1 thus in the first equation:
x1-3x3=-3
x1-9=-3
x1=-3+9
x1= 6
We solve for a thus in the second equation:
2x1+ax2-x3=-2
2+a2-x3=-2
a2-x3=-4
a2=-4+x3
The answer is: [D]: 11 1/2 .
___________________________________________________________
Explanation:
___________________________________________________________
2 7/8 <span>÷ 1/4 =
23/8 </span>÷ 1/4 = 23/8 * 4/1 ; The "4" cancels to a "1"; and the "8"
cancels to a "2"; (since "8÷4 =2" ;
and "4÷4 = 1" ;
__________________________________________________________
→ 23/8 * 4/1 = 23/2 * 1/1 = 23/2 * 1 = 23/2 = 11 1/2 ;
__________________________________________________________
→ which is: Answer choice: [D].
__________________________________________________________
Answer:
Top right option: g(x) = (x+1)(x-3)
Step-by-step explanation:
x=-1 is the solution to x+1=0
x=3 is the solution to x-3=0
Therefore, your expression so far is (x+1)(x-3) or x²-2x-3.
Since the vertex must be (1,-4) we must check if x=1 satisfies the equation x=-b/2a:
x=-b/2a
1=-(-2)/2(1)
1=2/2
1=1
Both sides are equal to each other, so the final function is g(x) = (x+1)(x-3)
Answer:
6 18/12 OR simplified 1 6/12
Step-by-step explanation:
1 1/4 + 5 5/6=
1 + 5 = 6
5/6 + 1/4
Mulitipy fraction by 3 and 2
15/12 + 3/12 = 18/12
18/12 = 1 6/12